Probiotics and muscle health: the impact of Lactobacillus on sarcopenia through the gut-muscle axis - Zhu, Jingjun; Peng, Fei; Yang, Huixin; Luo, Jing; Zhang, Li; Chen, Xiaolong; Liao, Huazhi; Lei, Hao; Liu, Shuai; Yang, Tingqian; Luo, Guanghua; Chen, Guodong; et al. (Frontiers in Microbiology, 2025)
Sarcopenia refers to the decline in skeletal muscle mass and function. Due to its increased mortality rate and severe disability, the clinical importance of sarcopenia is becoming increasingly prominent. Although the exact cause of sarcopenia is not fully understood, the gut microbiota (GM) plays a crucial role in the pathogenesis of sarcopenia, and increasing evidence suggests that gut dysbiosis may be associated with disease development. In the past few decades, the use of probiotics has surged, few studies have explored their impact on sarcopenia prevention and treatment. Lactobacillus probiotics are commonly used for gut health and immune support, but their mechanism in sarcopenia via the gut-muscle axis remains uncertain. This review highlights the treatment challenges, GM’s role in sarcopenia, and the potential of Lactobacillus as an adjunct therapy. In addition, we also discuss the possible mechanisms by which Lactobacillus affect muscle function, such as alleviating inflammatory states, clearing excessive reactive oxygen species (ROS), improving skeletal muscle metabolism, enhancing intestinal barrier function and modulating the gut microbiota and its metabolites. These mechanisms may collectively contribute to the preservation of muscle mass and function, offering a promising avenue for advancing microbial therapies for sarcopenia.